Revisão da tribo Onocephalini Thomson, 1860 (Insecta, Coleoptera, Cerambycidae, Lamiinae) - Batista, Luciano Vidal (2001)
The tribe Onocephalini Thomson, 1860, nowadays composed of four genera and twenty-three species, is revised in its totality. The studies were carried out through entomological material from collections of the Museu Nacional, Universidade Federal do Rio de Janeiro, Rio de Janeiro, of the Institut Royal des Sciences Naturelles de Belgique, Bruxelles and of the Muséum National d'Historie Naturelle, Paris. The tribe, as well as the the genera Onocephala Sturm, 1843, Perma Lacordaire, 1872, Pseudoperma Dillon & Dillon, 1946 and Stethoperma Lameere, 1884, and the species Onocephala diophthalma (Perty, 1832), Onocephala lineola Dillon & Dillon, 1946, revalidated, Onocephala albosignata sp. nov. (sent for publishing), Onocephala rugicollis Thomson, 1857, Perma aulica Lacordaire, 1872, Perma suturalis Bates, 1887, Perma lacordairei (Dillon & Dillon, 1946) comb. nov. (transferred fom Onocephala), Perma vittipennis Breuning, 1940, Pseudoperma chalcogramma (Bates, 1887), Pseudoperma olivacea sp. nov. (sent fr publishing), Pseudoperma patruelis (Breuning, 1940), Pseudoperma sanctipauli sp. nov. (sent fr publishing), Pseudoperma catarinensis sp. nov. (sent fr publishing), Pseudoperma straminea sp. nov. (sent fr publishing), Stethoperma batesi Lameere, 1884, Stethoperma zikani Melzer, 1923, Stethoperma duodilloni Gilmour, 1950,x Stethoperma obliquepicta Breuning 1940, Stethoperma multivittis Bates, 1887, Stethoperma candezei Lameere, 1884 and Stethoperma javovittata Breuning 1940, are studied ad described. The male terinalia is, fr the frst time, described and schematized and its chaacters are mentioned at tibal, generic and specifc leveis. A key fr identifcation of te genera ad four keys fr identifcation of the species are supplied. Two species of Onocephala ad four of Pseudoperma (all of tem mentioned above) are considered as new. The males of Perma lacordairei (Dillon & Dillon, 1946) comb. nov., and of Pseudoperma chalcogramma (Bates, 1887) ae characterized fr the frst time. Tree new synonymes {Onocephla tepahi Dillon & Dillon, 1946, syn. nov. [= Onocephala diophthlama (Perty, 1832)], Onocephala aulica Lucas, 1857, syn. nov. (= Onocephala rugicollis Thomson, 1857) and Onocephala thomsoni Dillon & Dillon, 1946, syn. nov. (= Perma suturalis Bates, 1887)}, a revalidaton and a new combination (one and oter referred above) are proposed. Lectotypes and paralectotypes are desigated fr Perma suturalis and Stethoperma batesi. The four syntypes of Perma suturalis are ftted into two genera and four diﬀerent species. The kown geogaphical distibution is mentioned fr tibe, genera and species. The cartogaphy of the taa are represented, and gaphs are provided, showing in percentage, the number of species by geogaphical locality. The biological and behavioural available data are supplied.